The use of collaboration and management to turn-around the performance of a failing copper mine - M Jacobs (The Australasian Institute of Mining and Metallurgy, 2022)
This abstract discusses a heap leach copper mine that was failing to perform and as a result was not meeting targeted production. The mine had numerous technical challenges including: high water inflows, low levels of geotechnical monitoring, performance issues with mining, resource model and grade control reconciliation issues, and unexplained low levels of performance from the heap leaching operations. A team from various organisations with specialist skill sets including: a forensic accountant, the owner’s representative and a mining engineer, was arranged to visit the site. The task was to investigate the situation and determine what could be done to turn the performance of the mine around. After an initial assessment in late 2018, efforts were directed to better understanding the operations and improving the performance of the site through preventative management. A key part included the creation of production forecasts that could be achieved that would help restore confidence in the operations. Uncertainty in the mine achieving production forecasts and the performance of the heap leaching operations were contributing to the decline of the operations. Investigations uncovered the fact that while the resource model could reliably predict total copper, a lack of sequential leach data meant the accurate prediction of soluble and insoluble copper species, both important for heap leaching, was difficult to do with any degree of certainty. The crushing and mining contractors also appeared to have suffered somewhat from a lack of management by the owner’s team and performance had affected the production of copper. Collaboration and management were used by the team to understand and stabilise the operations. Ongoing collaborative efforts by the management team, site personnel and contractors resulted in a positive outcome for the owners and their mine – and could at yours.